Specific Aspects of Forming the Professional Competence of Students in The Process of Higher Education Based on The Innovation Approach: Detailed method and Result Analysis - Xamidullaeva, Karimova Feruza; Fayzievna, Hakimova Muhabbat (Bumi Publikasi Nusantara, 2023)
In this article, ideas about specific aspects of the formation of professional competence in students based on innovative approaches and different orders in creativity are explained for supporting higher education. This study reported a detailed method with result analysis. The essence of the main content of the article is professional approaches to higher education and give them examples. This study can become a reference for practitioners, government, and stakeholders relating to higher education.